2023
DOI: 10.1021/acs.orglett.3c02927
|View full text |Cite
|
Sign up to set email alerts
|

A Tandem Madelung Indole Synthesis Mediated by a LiN(SiMe3)2/CsF System

Ruyuan Ma,
Yan-En Wang,
Dan Xiong
et al.

Abstract: A tandem Madelung indole synthesis by the reaction of methyl benzoate and N-methyl-o-toluidine has been discovered. The combination of LiN(SiMe 3 ) 2 with CsF is the key factor, which secures the high efficiency of such tandem transformations. Simply combining methyl benzoate, N-methyl-otoluidine LiN(SiMe 3 ) 2 , and CsF generated a diverse array of Nmethyl-2-phenylindoles (31 examples, 50−90% yields). Furthermore, the scalability and the poststructural modifications of this indole synthesis were demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…As their eternal interest in the synthesis of 2‐arylindoles is never got down, very recently Mao and co‐workers independently reported an altered tandem Madelung indole synthesis by employing methyl benzoates and N ‐methyl‐ o ‐toluidine (Scheme 27). [78] This protocol is compatible to halogens and methoxy substituents which is not realized by classical Madelung indole synthesis. Again, this methodology works well with LiN(SiMe 3 ) 2 in the presence of its larger sibling CsF to overcome the activation energy barrier.…”
Section: Annulationmentioning
confidence: 99%
“…As their eternal interest in the synthesis of 2‐arylindoles is never got down, very recently Mao and co‐workers independently reported an altered tandem Madelung indole synthesis by employing methyl benzoates and N ‐methyl‐ o ‐toluidine (Scheme 27). [78] This protocol is compatible to halogens and methoxy substituents which is not realized by classical Madelung indole synthesis. Again, this methodology works well with LiN(SiMe 3 ) 2 in the presence of its larger sibling CsF to overcome the activation energy barrier.…”
Section: Annulationmentioning
confidence: 99%
“…By using these bimetallic systems, a diverse array of transformations based on BnM (M = Li, Na, K, or Cs) has been demonstrated. Successful examples include the one-pot aminobenzylation of aldehydes with toluenes (Scheme a), one-pot preparation of 2-arylindoles from 2-fluorotoluenes and benzonitriles (Scheme b), tandem madelung indole syntheses from aromatic esters with N -methylbenzylamines, and many others . The convenient synthesis of indole in Scheme b involves chemoselective generation of benzylic carbanions with bimetallic systems and S N Ar reactions with unactivated aryl fluoride.…”
mentioning
confidence: 99%
“…Inspired by the above findings, we next explored three relatively mild bases MN­(SiMe 3 ) 2 (M = Li, Na, K) and found LiN­(SiMe 3 ) 2 was superior to other bases, giving 3aa in 18% yield (entry 3), which indicated that such transformation for chemoselective synthesis of indolin-3-ones is promising. Based on the benefits from the combination of MN­(SiMe 3 ) 2 (M = Li, Na) with Cs + , we screened the combinations of LiN­(SiMe 3 ) 2 with various cesium salts (entries 6–9). To our delight, the yield reached 88% with the combination of LiN­(SiMe 3 ) 2 and CsF, highlighting the essential role of cesium salts in such transformations (entry 6).…”
mentioning
confidence: 99%